Lifestyle, medication and socio-demographic determinants of mental and physical health-related quality of life in people with multiple sclerosis. Issue 1 (December 2016) - Jelinek, George; De Livera, Alysha; Marck, Claudia; Brown, Chelsea; Neate, Sandra; Taylor, Keryn; Weiland, Tracey
Abstract Background Health-related quality of life (QOL) is a key outcome for people with multiple sclerosis (MS). While modifiable lifestyle factors, like smoking, physical activity and vitamin D, have strong associations with development and progression of MS, few studies have examined such associations with QOL. Methods Using patient-reported data from 2312 people with MS from 54 countries, regression models explored associations of socio-demographic, therapeutic and lifestyle factors with QOL, using the Multiple Sclerosis Quality of Life-54 (MSQOL-54). Results Participants were on average 45.6 years old, 82.4% women, mostly partnered (74.1%), with a university degree (59.5%). Controlling for socio-demographic factors and disability, factors associated with better physical health composite (PHC) (on a 100 point scale) were: moderate and high physical activity compared to low (5.9 [95% confidence interval: 4.2, 7.6] and 9.9 [CI: 8.1, 11.6] points higher score respectively); non-smoking compared to current smoking (4.6 points [CI: 2.4, 6.7]); better diet (per 10 points on the 100 point Diet Habits Questionnaire scale (DHQ) 1.6 points [CI: 1.0, 2.2] points); normal body mass index (BMI) versus overweight or obese (2.1 points [CI: 0.4, 3.7] and 2.4 points [CI: 0.5, 4.3]); fewer comorbidities (4.4 points [CI: 3.9, 4.9]); and not taking a disease-modifying drug (DMD) (2.1 points [CI: 0.7, 3.4]). Better mental health composite (MHC) determinants were: moderate and high physical activity compared to low (4.0 points [CI: 2.0, 6.0] and 5.7 points [CI: 3.5, 8.0]); non-smoking compared to current (6.7 points [CI: 4.1, 9.3]); better diet (2.8 points [CI: 1.9, 3.5]); normal BMI versus overweight or obese (3.1 points [CI: 1.1, 5.1] and 3.5 points [CI: 1.3, 5.7]); meditating regularly (2.2 points [CI: 0.2, 4.2]); and no DMD use (2.9 points [CI: 1.3, 4.6]). Conclusions While causality cannot be concluded from cross-sectional data, the associations between modifiable lifestyle factors and QOL suggest significant potential for secondary prevention of the known deterioration of QOL for people with MS through lifestyle risk factor modification.